Controlled Release of Photoresponsive Nematic Liquid Crystalline Microcapsules. Issue 3 (3rd March 2021) - Iwai, Yosuke; Maeda, Takatoshi; Uchida, Yoshiaki; Araoka, Fumito; Nishiyama, Norikazu
Abstract : Nematic Liquid Crystalline Microcapsules In article number 2000079, Yoshiaki Uchida and co‐workers demonstrate the UV‐light‐triggered release of the contents of a water‐in‐oil‐in‐water double emulsion with a photo‐responsive nematic liquid crystalline shell. In the release process, the defects of the molecular orientational order, which are topologically essential for the shell sandwiched between the spherical interfaces, gather together, the shell deforms, and the inner water droplets are released to the outer phase.